Treatment allocation for linear models with covariate information - Tobias Aufenanger (Friedrich-Alexander-Universität Erlangen-Nürnberg, Institute for Economics, 2017)
This paper analyses optimal treatment allocation of experimental units to treatment and control group. 'Optimal' means that the allocation of treatments should balance covariates across treatment and control group in a way that minimizes the variance of the treatment estimator in a given linear model. This paper shows the benefits as well as the limits of this approach. In particular, it presents a sample size formula as well as several simulations to give some intuition on the minimum as well as the maximum benefits of this approach compared to random allocation as well as to alternative methods of treatment allocation.
Is replaced by the following version: http://hdl.handle.net/10419/179521
Keywords: C90; C61; 330; experiment design; treatment allocation